CURRENT IDEAS ABOUT THE PATHOGENETIC MECHANISMS OF PAIN IN OSTEOARTHROSIS - E. F. Turovskaya; L. I. Alekseeva; E. G. Filatova (Научно-практическая ревматология)
The literature review presents the current idea about the mechanisms of chronic pain. Experimental and clinical studies of the mechanism of chronic pain in osteoarthrosis (OA), which show that dysfunction of pain systems themselves (the so-called dysfunctional pain) along with the nociceptive mechanisms caused by chronic inflammation and degenerative changes in the joint area plays an important role in the chronization of pain syndrome, are considered in detail. Identification of the dysfunctional mechanisms of chronic pain in OA allows an understanding of the dissociations existing between the intensity of pain and the degree of structural changes in the joint. The paper also attempts to detect comorbidities that may be additionally involved in the development of pain. Effective ways to treat OA are outlined.